2020
DOI: 10.1111/jam.14651
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the species of Campylobacter colonizing chickens reared for meat

Abstract: Aim To investigate factors influencing Campylobacter spp. colonization of broiler chickens. Methods and Results Campylobacters were isolated from caeca from 319 flocks of two different breeds (199 Cobb and 120 Hubbard), reared as standard (199), Freedom Food/corn fed (57), free‐range (47) or organic (16). The standard category exclusively used Cobb birds slaughtered at 38‐41 days. The Freedom Food/corn‐fed and free‐range Hubbard birds were slaughtered at 49–56 days and the organic flocks at 70 days. Campylobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Caffrey et al (2021) recently identified a correlation between breed and Campylobacter , with flocks comprised of Cobb birds, or a mixture of Cobb and Ross birds 4.75 times more likely to test positive for fluoroquinolone resistant Campylobacter jejuni than flocks comprised of just Ross birds. Further to this, Cobb birds have been found to be more frequently colonized by Campylobacter than Hubbard birds by Babacan et al (2020), however they were unable to separate this association from other rearing factors such as age-of-slaughter. Our Bayesian network analysis, similar to the hock burn conclusions, was unable to detect any direct arc of causation between Breed and Campylobacter colonization, suggesting that the breed of chicken is indicative of the company managing the flock, and not necessarily an indicator of a breed-specific susceptibility.…”
Section: /38mentioning
confidence: 89%
See 2 more Smart Citations
“…Caffrey et al (2021) recently identified a correlation between breed and Campylobacter , with flocks comprised of Cobb birds, or a mixture of Cobb and Ross birds 4.75 times more likely to test positive for fluoroquinolone resistant Campylobacter jejuni than flocks comprised of just Ross birds. Further to this, Cobb birds have been found to be more frequently colonized by Campylobacter than Hubbard birds by Babacan et al (2020), however they were unable to separate this association from other rearing factors such as age-of-slaughter. Our Bayesian network analysis, similar to the hock burn conclusions, was unable to detect any direct arc of causation between Breed and Campylobacter colonization, suggesting that the breed of chicken is indicative of the company managing the flock, and not necessarily an indicator of a breed-specific susceptibility.…”
Section: /38mentioning
confidence: 89%
“…While disappointing to not ascertain the primary root cause of increased Campylobacter prevalence from within our considered set of variables, the work has revealed a key network of dependencies within commonly recorded and studied metrics. While far from the first study to examine the contributions of multiple health factors towards Campylobacter colonization (Babacan et al, 2020;Frosth et al, 2020;Humphery et al, 1993;Rushton et al, 2009), our work is the first, to our knowledge, to utilise the powerful methodologies underlying Bayesian network analysis in studying the spread of Campylobacter. Such approaches, in combination with more traditional logistic regression analyses, greatly increase the descriptive power of gathered datasets, and it is our hope that this work will help expedite their adoption throughout the field of Campylobacter risk management.…”
Section: /38mentioning
confidence: 99%
See 1 more Smart Citation
“…The colonization of broiler intestine with C. jejuni/coli depends on several factors, including breed, animal density, special diet, or access to the outside. [15][16][17]. Moreover, individual farm characteristics, such as poor biosecurity (e.g., inadequate hygiene measures, access of vectors), the presence of other animal species on the farm, catching and placing measures and management of crates have been shown to increase C. jejuni/coli colonization and excretion rates of broilers [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is critical to control the growth of microorganisms, especially during commercial poultry processing, as it influences the shelf life and quality of carcass products (Babacan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%